2020
DOI: 10.3390/ijms21218368
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Carbohydrates and Lipids in the Pathogenesis of Leaky Gut Syndrome: An Overview

Abstract: This review summarizes the recent knowledge on the effects of dietary carbohydrates and lipids on the pathophysiology of leaky gut syndrome (LGS). Alterations in intestinal barrier permeability may lead to serious gastrointestinal (GI) disorders. LGS is caused by intestinal hyperpermeability due to changes in the expression levels and functioning of tight junctions. The influence of dietary habits on intestinal physiology is clearly visible in incidence rates of intestinal diseases in industrial and developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 101 publications
(133 reference statements)
0
35
0
4
Order By: Relevance
“…The tight junction (TJ), which controls the integrity and permeability of intestinal epithelium, is composed of the TJ proteins such as Occludin, zonula occludens-1 (ZO-1), Claudin-1 and Claudin-4 ( Bai et al., 2020 ). Moreover, disruptions in the tight junction barrier lead to impair the gut epithelial barrier function, which are involved in the pathogenesis of many intestinal disorders ( Binienda et al., 2020 ). We found that CB RH2 administration, especially in high dose, upregulated intestinal mRNA levels of Occludin and ZO-1 ( Figure 4 ), which was consistent with previous studies ( Xiao et al., 2018 ; Liu et al., 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…The tight junction (TJ), which controls the integrity and permeability of intestinal epithelium, is composed of the TJ proteins such as Occludin, zonula occludens-1 (ZO-1), Claudin-1 and Claudin-4 ( Bai et al., 2020 ). Moreover, disruptions in the tight junction barrier lead to impair the gut epithelial barrier function, which are involved in the pathogenesis of many intestinal disorders ( Binienda et al., 2020 ). We found that CB RH2 administration, especially in high dose, upregulated intestinal mRNA levels of Occludin and ZO-1 ( Figure 4 ), which was consistent with previous studies ( Xiao et al., 2018 ; Liu et al., 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate fermentation yields dietary fibers that are a primary source of energy for gut microbiota 23 . Defects in glucose metabolism may contribute to disease progression in ALS 24 .…”
Section: Changes Of Carbohydrate In the Sod1 G93a Micementioning
confidence: 99%
“…The intestinal epithelium is the second most extensive physical barrier in the human body, just second to the skin ( 2 ). As a barrier, its function is to selectively allow the absorption of nutrients, prevent pathogen invasion, prevent loss of water and electrolytes, and allow the exit of waste ( 3 ). In addition, the intestinal epithelium is currently recognized as the central axis of mucosal immunity as it is estimated that the gut houses up to 70% of the body’s lymphocyte population, making it the largest immune organ in humans ( 4 ).…”
Section: Anatomy Of Epithelia-malt In Oral and Gi Tractsmentioning
confidence: 99%
“…The microbiota residing in the outer gut layers can promote the growth of pathogenic strains but also stimulate biochemical pathways that preserve the structure and function of the intestine. For example, Mucin 2 (MUC2) specifically protects the epithelium from inflammation and thus from multiple disease exacerbation ( 3 ). Microorganisms in the outer mucus layer use MUC2 as an energy source, which in turn can lead to mucin-degrading bacteria expanding in the microbiome, thus increasing the degradation of internal mucus ( 22 ).…”
Section: Anatomy Of Epithelia-malt In Oral and Gi Tractsmentioning
confidence: 99%